Medical negligence compensation claims in knee meniscal surgery in Norway: a cross-sectional study - Frank-David Øhrn; Asbjørn Årøen; Tommy Frøseth Aae (Patient Safety in Surgery)
Abstract Background Meniscal surgery is one of the most frequent orthopaedic procedures performed worldwide. There is a wide range of possible treatment errors that can occur following meniscal surgery. In Norway, patients subject to treatment errors by hospitals and private institutions can file a compensation claim free of charge to the Norwegian System of Patient Injury Compensation (NPE). The purpose of this study was to systematically analyse compensation claims filed to the NPE following meniscal surgery and evaluate gender effects on accepted claims. Our hypothesis was that there was no gender difference in accepted claims. Methods We performed a cross-sectional study assessing all registered claims at the NPE after meniscal surgery from 2010 to 2020. The surgical procedures were stratified into subgroups following data collection. Data from the Norwegian Patient Registry were collected to obtain information on the numbers of the different procedures performed in hospitals and private institutions. We calculated frequencies and relative frequencies of categorical data. Differences in categorical data were calculated using the Pearson Chi-square test. Results The total number of meniscal resections and sutures in the study period was 119,528. A total of 372 compensation claims were filed, 241 male and 130 female. Of these, 152 (40.9%) claims were accepted, while 220 (59.1%) were rejected. The most frequent reasons for filing a compensation claim were pain (114), followed by infection (98), wrong technique (38) and impaired function/instability (25).There was a significant gender difference in the acceptance of claims in favour of men (121 vs. 31, p < 0.001). A sensitivity analysis excluding infection as reason for compensation claim found no gender difference (p = 0.16) in acceptance of claims. Conclusion Compensation claims after meniscal surgery are rare, with only 0.3% of patients filing a compensation claim. There was a marked preponderance of men with accepted claims due to a higher frequency of postoperative infections. Surgeons should be aware of this and take this into account in the decision-making before surgery.